[18F]‐Sodium Fluoride PET/MR Imaging for Bone–Cartilage Interactions in Hip Osteoarthritis: A Feasibility Study. Issue 12 (30th August 2019) - Tibrewala, Radhika; Bahroos, Emma; Mehrabian, Hatef; Foreman, Sarah C.; Link, Thomas M.; Pedoia, Valentina; Majumdar, Sharmila
ABSTRACT: This study characterized the distribution of [ 18 F]‐sodium fluoride (NaF) uptake and blood flow in the femur and acetabulum in hip osteoarthritis (OA) patients to find associations between bone remodeling and cartilage composition in the presence of morphological abnormalities using simultaneous positron emission tomography and magnetic resonance imaging (PET/MR), quantitative magnetic resonance imaging (MRI) and femur shape modeling. Ten patients underwent a [ 18 F]‐NaF PET/MR dynamic scan of the hip simultaneously with: (i) fast spin‐echo CUBE for morphology grading and (ii) T 1 ρ / T 2 magnetization‐prepared angle‐modulated partitioned k ‐space spoiled gradient echo snapshots for cartilage, bone segmentation, bone shape modeling, and T 1 ρ / T 2 quantification. The standardized uptake values (SUVs) and Patlak kinetic parameter ( K pat ) were calculated for each patient as PET outcomes, using an automated post‐processing pipeline. Shape modeling was performed to extract the variations in bone shapes in the patients. Pearson's correlation coefficients were used to study the associations between bone shapes, PET outcomes, and patient reported pain. Direct associations between quantitative MR and PET evidence of bone remodeling were established in the acetabulum and femur. Associations of shaft thickness with SUV in the femur ( p = 0.07) and K pat in the acetabulum ( p = 0.02), cam deformity with acetabular score ( p = 0.09), osteophytic growth on the femur head with K pat ( p = 0.01) were observed. Pain had increased correlations with SUV in the acetabulum ( p = 0.14) and femur ( p = 0.09) when shaft thickness was accounted for. This study demonstrated the ability of [ 18 F]‐NaF PET‐MRI, 3D shape modeling, and quantitative MRI to investigate cartilage‐bone interactions and bone shape features in hip OA, providing potential investigative tools to diagnose OA. © 2019 The Authors. Journal of Orthopaedic Research ® published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society J Orthop Res 37:2671–2680, 2019